2011
DOI: 10.1007/s10237-010-0284-9
|View full text |Cite
|
Sign up to set email alerts
|

A determination of the minimum sizes of representative volume elements for the prediction of cortical bone elastic properties

Abstract: At its highest level of microstructural organization-the mesoscale or millimeter scale-cortical bone exhibits a heterogeneous distribution of pores (Haversian canals, resorption cavities). Multi-scale mechanical models rely on the definition of a representative volume element (RVE). Analytical homogenization techniques are usually based on an idealized RVE microstructure, while finite element homogenization using high-resolution images is based on a realistic RVE of finite size. The objective of this paper was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 28 publications
5
64
0
Order By: Relevance
“…It was found that the minimum RVE size should be about half a millimetre. This value is coherent with the findings of other authors (Grimal et al 2011a) who have addressed this issue using different approaches. Moreover, within the RVE, our model assumes homogeneous material properties around the pores at the tissue scale.…”
Section: The Multiscale Model: a Compromise Between Accuracy And Simpsupporting
confidence: 93%
“…It was found that the minimum RVE size should be about half a millimetre. This value is coherent with the findings of other authors (Grimal et al 2011a) who have addressed this issue using different approaches. Moreover, within the RVE, our model assumes homogeneous material properties around the pores at the tissue scale.…”
Section: The Multiscale Model: a Compromise Between Accuracy And Simpsupporting
confidence: 93%
“…This volume should be large enough to statistically represent the whole structure and, at the same time, sufficiently small to enable a computationally feasible approach for the actual computation of the effective elasticity tensor. This can be achieved by performing elastic-type computations on a representative volume element (RVE), which, by definition, satisfies Hill's condition [17,18], i.e., the coarse scale energy (which involves the effective elastic properties) equals the average fine scale energy (see, e.g., [14] for a practical application of the RVE technique for cortical bone). Further average field techniques involve the well-known results by Eshelby [12], i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Schapery's based his approach on an iso-strain behaviour of fibres and matrix. Equation (15) and Equation (16) show the calculation of longitudinal and transverse coefficients of thermal expansion in Schaperys model:…”
Section: Comparison Of the Results With Analytical Modelsmentioning
confidence: 99%
“…RVE concept not only can be used in man-made composite material, natural material, e.g. bones are often described using this concept (see, among others [15,16,17,18]). …”
Section: Methodsmentioning
confidence: 99%